THE IMPACTS OF COMMUNICATIVE COMPETENCE ON SECOND LANGUAGE ACQUISITION AND EMPLOYING CERTAIN METHODS TO IMPROVE SPEAKING SKILLS - Alimatova Sevarakhon (University Research Base, 2024)
This study explores the impact of communicative competence on second language acquisition, challenging traditional grammar-focused methods by employing Effortless English lessons to enhance speaking abilities among learners. Drawing on theories from notable scholars such as Chomsky, Hymes, Canale, and Swain, the research aims to demonstrate that integrating communicative competence into language teaching significantly improves students' oral skills. Through a combination of interviews, pre-tests, and the application of the Effortless English method, findings suggest that a communicative approach not only bolsters learners' confidence and interaction but also fosters a more engaging and effective learning environment. This investigation highlights the necessity of moving beyond conventional teaching techniques to embrace methods that prioritize real-world communication skills, thus preparing students for more authentic and practical language use.